Assessing Barriers in Surveillance Colonoscopy in Patients with Pathological Findings - Jaboori, Khalid (My University, 2015)
Significance: Among men and women, colorectal cancer is the third leading cause of cancer related deaths in the United States. 1 Tragically, most colorectal cancer is preventable, and due to barriers that exist, only 4 out of 10 colorectal cancers that should be diagnosed, are diagnosed in early stages.1 Purpose: The purpose of this study was to assess potential barriers that exist in colorectal cancer surveillance. The population chosen reflects those individuals that require average risk surveillance colonoscopy per the United States Preventative Services Task Force (USPSTF) guidelines.2 Very little research on surveillance colonoscopy barriers was present upon literature review. The researchers hypothesized that additional barriers may exist based on the paucity of current data. Methods: This study was a retrospective chart review of medical records from 2005-2009 with a survey arm that interviewed 331 patients via phone with a pre-validated questionnaire based on reviewed medical records. Information was gathered and analyzed using univariate analysis with Chi Square testing and multivariate logistical regression with SPSS V 22 to assess for possible barriers to obtaining a surveillance colonoscopy. Results: Results showed that similar barriers to screening colonoscopy exist with surveillance colonoscopy. In addition, potential significant barriers such as perceived pain of initial colonoscopy, ease of scheduling an appointment, and proper notification were identified as factors to adequate patient follow up. Conclusions: Although certain specific barriers (such as difficulty scheduling an appointment, not knowing a patient needed to receive a colonoscopy by the medical provider and patient themselves, level of comfort during the procedure, or level of comfort during the prep the night before the colonoscopy) were identified, more research needs to be done into potential additional barriers that may exist. Additionally, automation of medical records to allow patient notification of the need of colonoscopy by providers to patients must be developed.
Thesis (Master's)--University of Washington, 2015
Keywords: barriers; colonoscopy; surveillance; Medicine; Public health; health services